2019
DOI: 10.3389/fneur.2019.01199
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Corticoreticulospinal Tract Injuries According to Whiplash in Mild Traumatic Brain Injury Patients

Abstract: Background: This study investigated differences in postural control ability (PCA) and corticoreticulospinal tract (CRT) injury severity according to whiplash in patients with mild traumatic brain injury (mTBI).Methods: Thirty-one patients with mTBI and 21 healthy control subjects were recruited for this study. The balance error scoring system (BESS) was used for PCA assessment. Based on their whiplash history, the patients were classified into two groups: group A—mTBI with whiplash injury; group B—mTBI without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In 1998, Shannon et al [20] reported that axonal injury was detected on post-mortem brain dissection in 14 children with shaken baby syndrome. After introduction of DTI, several studies using DTT demonstrated TAI following whiplash injury in patients with mild TBI [21][22][23][24][25][26][27]. In 2019, Jang and Seo reported on two patient with mild TBI who showed injury of STT with central pain following whiplash injury [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1998, Shannon et al [20] reported that axonal injury was detected on post-mortem brain dissection in 14 children with shaken baby syndrome. After introduction of DTI, several studies using DTT demonstrated TAI following whiplash injury in patients with mild TBI [21][22][23][24][25][26][27]. In 2019, Jang and Seo reported on two patient with mild TBI who showed injury of STT with central pain following whiplash injury [23].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Jang and Seo reported on two patient with mild TBI who showed injury of STT with central pain following whiplash injury [23]. From 2015 to 2019, Jang et al [21][22][23][24][25][26][27] reported several manuscripts of TAI using DTT in the patient (suffering tremor, ataxia, hypersomnia, impaired motor function, tinnitus and neural pain) with neural tract injury such as DRTT, ARAS, Corticospinal tract (CST), CRT, AR and STT after whiplash injury. Therefore, to the best of our knowledge, this is the first original study to demonstrate the STT injury in large number of patients after whiplash injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation